Clinicopathologic characteristics of severe COVID-19 patients in Mexico City: A post-mortem analysis using a minimally invasive autopsy approach. - Carlos Nava-Santana; María Rodríguez-Armida; José Víctor Jiménez; Nancy Vargas-Parra; Diana E Aguilar León; Alejandro Campos-Murguia; Ricardo Macías-Rodriguez; Andrés Arteaga-Garrido; Antonio C Hernández-Villegas; Guillermo Dominguez-Cherit; Eduardo Rivero-Sigarroa; Armando Gamboa-Dominguez; et al. (PLoS ONE, 2022)
Objective Describe the histological findings of minimally ultrasound-guided invasive autopsies in deceased patients with severe SARS-CoV-2 and compare the diagnostic yield with open autopsies. Design Observational post-mortem cohort study. Minimally invasive ultrasound-guided autopsies were performed in fourteen deceased patients with a confirmed diagnosis of SARS-CoV-2 pneumonia. Histological and clinical findings of lung, kidney, and liver tissue are described and contrasted with those previously reported in the literature. Setting Single-center COVID-19 reference center in Mexico City. Results Fourteen minimally invasive autopsies revealed a gross correlation with open autopsies reports: 1) Lung histology was characterized mainly by early diffuse alveolar damage (12/13). Despite low lung compliances and prolonged mechanical ventilation, the fibrotic phase was rarely observed (2/13). 2) Kidney histopathology demonstrated acute tubular injury (12/13), interstitial nephritis (11/13), and glomerulitis (11/13) as the predominant features 3) Liver histology was characterized by neutrophilic inflammation in all of the cases, as well as hepatic necrosis (8/14) despite minimal alterations in liver function testing. Hepatic steatosis was observed in most cases (12/14). SARS-CoV-2 positivity was widely observed throughout the immunohistochemical analysis. However, endothelitis and micro thrombosis, two of the hallmark features of the disease, were not observed. Conclusion Our data represents the largest minimally invasive, ultrasound-guided autopsy report. We demonstrate a gross histological correlation with large open autopsy cohorts. However, this approach might overlook major histologic features of the disease, such as endothelitis and micro-thrombosis. Whether this represents sampling bias is unclear.